Designing rubrics for reading and language arts - Groeber, Joan F. (Arlington Heights, IL : SkyLight Professional Development, 2003)
If you are a reading and language arts teacher seeking model rubrics for performance assessment with clear instruction on how to create teacher-made rubrics, then "Designing Rubrics For Reading And Language Arts" is for you! Performance levels and the task objectives are identified in each rubric to help reduce subjectivity in grading and help students set goals for their own achievement. The author provides teachers in all grade levels with sample rubrics to assess student proficiency in language arts and in all genres, including nonfiction. Teachers can follow the step-by-step instructions for creating their own rubrics to meet their students' instructional needs.
Includes bibliographical references and index.
Keywords: Language arts -- Ability testing -- United States; Reading -- Ability testing -- United States; Competency based educational tests -- United States